Pengaruh Electronic Word Of Mouth (E-WOM) dan Persepsi Harga Terhadap Minat Beli Melalui Aplikasi Shopee Pada Mahasiswa Di Gresik - Dwiyanti, Ferika; Rejeki, Asri; Puspitaningrum, Noer Suci Endah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of electronic word of mouth (e-wom) and price perceptions on buying interest through the Shopee application. This research uses a quantitative research type, with a correlational method. Respondents in this study were students in Gresik. The sampling technique with Non Probability Sampling is Incidental Sampling. A total of 120 respondents. Test the validity of the scale using content validity. Reliability test using Alpha Cornbach. Data analysis using multiple linear regression test with IBM Statistical Program For Social Science (SPSS) for windows version 26. The results of this study are that there is a simultaneous influence between electronic word of mouth and price perception on buying interest through the shopee application on students in Gresik with significance value of 0.000 (p <0.05). In the regression test analysis obtained a significance value of 1.278 (p> 0.05), which means that there is an influence between electronic word of mouth on buying interest, so h2 is accepted. Regression test obtained a significance value of 0.329 (p <0.05), which means that there is no influence between price perceptions and buying interest. The results of the Square Test (R2) show a number of 0.350, which means that the electronic word of mouth (e-WOM) variable and the price perception variable contribute 35% to the buying interest variable, while the remaining 65% is influenced by other variables that were not studied in this research